Management of Initial Convergence Events at Broadmeadow Mine - R. J. Coutts; D. G. Lynch; M. R. Martin (International Conference on Ground Control in Mining, 2018)
"Broadmeadow Mine is an underground longwall mine located in Central Queensland, Australia. The mine introduced a top coal caving (TCC) longwall face in 2013 but since then has experienced severe convergence events at the start of each panel after 60–70m of retreat, resulting in equipment damage and the longwall almost becoming iron bound. A significant geotechnical monitoring effort during LW10 and LW11 to characterise the caving mechanics and operational changes during LW11 were successful in mitigating the risk posed by these initial convergence events. This paper describes the geotechnical monitoring programme undertaken during LW11, the operational methods used to mitigate these initial convergence events, and the contribution to these events of the TCC technique.A thick sandstone unit close to the extraction roof was likely the cause of the convergence events at the start of each longwall panel. However, stress change monitoring cells, surface extensometers, an inclinometer, and the blockage of holes designed for pre-conditioning using hydraulic fracturing indicated that the convergence events were not caused by the sudden collapse of sandstone bridging across the goaf. Rather, they were caused by the propping action of strong units within the overburden strata. Equipment design modifications were made to allow the longwall to remain operational during the convergence events and an operational strategy was implemented to mitigate convergence in LW11. The initial convergence event was successfully negotiated, and Broadmeadow went on to be the highest producing longwall for CY16 in Australia.INTRODUCTIONBroadmeadow Mine is an underground longwall mine located in Central Queensland, Australia, owned and operated by BHP Mitsubishi Alliance (BMA). The mine is a punch longwall mine using open cut pit access provided by Goonyella/Riverside Mine. Broadmeadow commenced longwall operations in 2005 using a conventional high reach longwall, but later changed to the top coal caving (TCC) method of extraction. Broadmeadow extracts the easterly dipping 5.5–7.5m-thick Goonyella Middle Seam in ranging in depth from 90m to 330m. The coal is washed and blended at the adjacent Goonyella/Riverside open cut mine to produce a premium coking coal product for export."